الكتابة ودورها في إبراز المظاهر الحضارية لمصر الفرعونية 3200 ق.م – 300م - باهي، بلال, مباركي، العيد (جامعة الوادي university of Eloued, 2019)
الملخص: وكانت إشكالية البحث لإلى أي مدى استطاعت الكتابة الرقي بحضارة مصر القديمة ؟ وماهو الدور الذي قدمته في التفاعلات الحضارية ؟ - ولقد كانت الإجابة عن الإشكالية بمدخل وثلاث فصول حيث تضمن المدخل الإطار الجغرافي والتاريخي لمصر ، - أما الفصل الأول بحيث تطرقنا فيه البدايات الأولى للكتابة المصرية وتطورها مع أهم مصدر لها وهو حجر الرشيد مع جملة من الخصائص لها ، - أما الفصل الثاني فتضمن الكتابات التي عرفتها مصر قديما وكانت البداية مع الكتابة الهيروغليفية بحيث كانت أهم كتابة وتليها الكتابة الديموطيقية والكتابة الهيراطيقية وأخر كتابة هي القبطية ، بحيث قمنا بتعريف مع ذكر كل خصائص وما تتميز به كل كتابة عن الأخرى كما قمنا بتقديم نماذج عن الكتابات الأربعة مع صور توضيحية من كل نوع . - وجاء الفصل الثالث والذي عنوانه أهمية الكتابة في ابراز المظاهر الحضارية بحيث تناولنا أربع عناصر : الجانب السياسي بحيث أوضحنا فيه كيفية نهوض الكتابة بالحياة السياسية في مصر . الجانب العسكري والذي يعتبر العامل العسكري الذي يعتبر العامل الرئيسي للحفاظ على الحياة السياسية . الجانب الاقتصادي بحيث تمثل في الزراعة والتجارة والصناعة وعلاقتهم بالكتابة خصوصا في المبادلات التجارية لمصر مع جيرانها . الجانب الاجتماعي بحيث قمنا بشرح التركيبة الاجتماعية التي يتكون منها والتي قسمنا بناءا على ما جاء في النصوص الملكية والنصوص الأدبية . الجانب الديني حيث توصلنا الى معرفة الحياة الدينية من خلال الطقوس الجنائزية والاعتقادات المصرية القديمة . وفي الاخير استنتجنا بعض النقاط بإدراجها في الخاتمة : ان من بزوغ نور الحضارة المصرية القديمة والعوامل جغرافية التي اضفت عليها الطابع الحضاري العظيم وكان من ابرز العوامل موقع مصر بحيث تتوسط القارتين الافريقية والآسيوية . توصل المصري الى ابتكار الكتابة بحيث قام بتدوين اعماله بحيث تضمن لها القدرة بوصل الماضي بالحاضر وتوريث الانتاج الحضاري على مر الاجيال . عملت الكتابة على توصيل خلق لغة يتخاطب بها المجتمع المصري . Résumé :فرنسية أو انجلزية The problem of research was to what extent was it able to write in the ancient civilization of Egypt? What role did it play in cultural interactions? - The answer to the problem with the entrance and three chapters where the portal included the geographical and historical framework of Egypt, - The first chapter, where we touched on the first beginnings of Egyptian writing and its development with the most important source is a good stone with a set of characteristics, The second chapter includes the writings of ancient Egypt. The beginning was written with hieroglyphic writing. The most important writing, followed by the demotic script, the hieratic writing and the last writing, is the Coptic, so we defined all the characteristics and characteristics of each writing. With illustrations of each kind. - The third chapter, which is entitled the importance of writing in highlighting the manifestations of civilization so that we dealt with four elements: The political aspect in which we explained how the rise of writing in political life in Egypt. The military aspect, which is considered the military factor, which is the main factor to preserve political life. The economic aspect is represented in agriculture, trade, industry and their relationship to writing, especially in the trade relations of Egypt with its neighbors. Social aspect so that we explained the social structure that consists of which we divided according to what is written in the royal texts and literary texts. The religious side where we came to know the religious life through funerary rituals and ancient Egyptian beliefs. In the latter, we concluded some points by including them in the conclusion: That the emergence of the light of ancient Egyptian civilization and geographical factors that have been added to the great civilization and was one of the most prominent factors in the location of Egypt to mediate the continents of Africa and Asia. Al-Masri came to invent the writing so that he recorded his works so as to guarantee her the ability to connect the past with the present and to inherit the cultural output over generations. The writing worked to connect the creation of a language in which the Egyptian society is addressing
مذكرة ماستر تاريخ تخصص تاريخ الحضارات القديمة
Keywords: الكتابة المصرية القديمة، الحضارة الفرعونية، الحضارة المصرية